A Controlled Trial of Noninvasive Positive Pressure Ventilation (NIPPV) in Patients of COPD with Respiratory Failure (Bangladesh Critical Care Journal, 2013)
Objective : To assess the role of noninvasive positive pressure ventilation (NIPPV) in patients of acute exacerbation of COPD with respiratory failure, also to reduce endotracheal intubation (ETI) and the frequency of complications associated with ETI. Materials and Methods : Prospective, single blind, randomized controlled trial study (RCT) comparing the effect of combined standard medical treatment and noninvasive positive pressure ventilation with standard medical treatment alone in patients admitted to National Institute of Diseases of the Chest and Hospital (NIDCH), Mohakhali, Bangladesh over a 12-month period. Results : A total number of 60 patients of acute exacerbation of COPD with type II respiratory failure were enrolled from inpatient department of Institute of Diseases of the Chest and Hospital (NIDCH), Mohakhali, Bangladesh. A total of 30 (thirty) were randomly assigned to standard therapy and 30 (thirty) to noninvasive ventilation. The two groups had similar clinical characteristics on admission to the hospital. The use of noninvasive ventilation significantly reduced the need for endotracheal intubation (which was dictated by objective criteria): 12 of 30 patients (40.0%) in the noninvasive- ventilation group were intubated, as compared with 22 of 30 patients (73.3%) in the standard-treatment group (P=0.01). In addition, the frequency of complications was significantly lower in the noninvasive-ventilation group. The mean ( ± SD) hospital stay was significantly shorter for patients receiving noninvasive ventilation. 19.2±5.7days vs. 23.5±8.3 days, (P 0.02). The in-hospital mortality rate was also significantly reduced with noninvasive ventilation, 5 of 30 patients (16.7%) in the noninvasive- ventilation group died in the hospital, as compared with13 of 30 (43.3%) in the standard-treatment group( P 0.04) Conclusions : In selected patients with acute exacerbations of chronic obstructive pulmonary disease, noninvasive ventilation can reduce the need for endotracheal intubation, complications, the length of the hospital stay, and the in-hospital mortality rate. DOI: http://dx.doi.org/10.3329/bccj.v1i2.17201 Bangladesh Crit Care J September 2013; 1 (2): 86-92